Why not strangers? - Zhang, Yan (My University, 2020)
As inherently social animals, human are made happier and healthier when connected to others (Stark, 2016). We are used to be connected tightly with our acquaintances, but usually ignore that, strangers, as a product of urbanization, is also an important component of our social relationship in modern society. What we can see today is that so many people are afraid of or don’t bother to have interactions with strangers. People waiting at the bus stations stare at their mobile phone screens without even making eye contact with each other. Two persons meeting on the same sidewalk don’t smile to each other. Even people who live in the same neighbourhood avoid having any interaction when they see each other in the garden. People are so used to stay in their own “safety bubble” and be self-isolated. This thesis aims to enhance the experience of urban life within the context of public spaces, by exploring and promoting the interactions between strangers with the respect of social distance in modern society. For most people living in cities, they have their expected daily narratives. Public spaces for them have become more and more like a space where they will only pass by while commuting between home and office and urban life is missing. According to Goffman(1956) and his dramaturgical theory, people usually have different performances in front of different groups of acquaintances, while interactions with strangers can be a relaxed and unexpected experience in your daily life. In this thesis, how people behave and interact in public spaces will be discussed. After some research about sociology, psychology and human behavior, several relevant agents and design elements will be selected as focus of the design. Prototypes will be built as proposed physical environment and discussion about colour, materiality, and program will come after that. The result will be a sequence of public spaces where some architectural elements will be designed as interruptions or attractions. People can feel easy to have some unexpected interactions with strangers and thus, feel better connected to others.
Keywords: interactions of the unacquainted, urban life, public spaces, elemental architecture